Ras-independent transformation by v-Src - Aftab, Dana T. (The National Academy of Sciences of the USA, 1997)
Signaling by a variety of receptor and nonreceptor tyrosine kinases is mediated by Ras, a membrane-associated GTPase. Expression of v-Src, a transforming nonreceptor tyrosine kinase, results in Ras activation, and inhibition of Ras function in NIH 3T3 cells suppresses transformation by v-Src, indicating that in these cells Ras-dependent signaling pathways are required for v-Src to exert its biological effects. However, we show here that Ras was not activated in Rat-2 fibroblasts transformed by wild-type v-Src, or in chicken embryo fibroblasts transformed by SRX5, a v-Src mutant with a linker insertion at the major site of autophosphorylation. Expression of a dominant-negative mutant of Ras completely inhibited the ability of v-Src to activate the mitogen-activated protein kinase ERK2, which is downstream of Ras. However, dominant-negative Ras did not suppress transformation by v-Src as judged by a variety of criteria. Thus, v-Src can transform at least some cell types in the absence of Ras activation or Ras-stimulated ERK2 activity, and in these cells activation of Ras-independent signaling pathways must therefore be sufficient for transformation.